Metabolomic approach to search for fungal resistant forms of Aegilops tauschii Coss. from the VIR collection - T. V. Shelenga; L. L. Malyshev; Yu. A. Kerv; T. V. Diubenko; A. V. Konarev; V. I. Horeva; M. K. Belousova; M. A. Kolesova; N. N. Chikida (Вавиловский журнал генетики и селекции)
Broadening of the genetic diversity of donors of resistance to biotic environmental factors is a challenging problem concerning Triticum L., which can be solved by using wild relatives of wheat, in particular, Aegilops tauschii Coss., in breeding programs. This species, believed to be the donor of D genome of common wheat (T. aestivum L.), is a source of some traits important for breeding. This greatly facilitates the possibility of crossing Ae. tauschii with common wheat. Aegilops L. species are donors of effective genes for resistance to fungal diseases in wheat. For instance, genes that determine resistance to rust agents in common wheat were successfully introgressed from Ae. tauschii into the genome of T. aestivum L. The aim of our study was to identify differences in metabolomic profiles of Ae. tauschii forms (genotypes), resistant or susceptible to such fungal pathogens as Puccinia triticina f. sp. tritici and Erysiphegraminis f. sp. tritici.These indicators may be used as biochemical markers of resistance. A comparative analysis of groups of Ae. tauschii accessions showed that metabolomic profiles of the forms with or without resistance to fungal pathogens differed significantly in the contents of nonproteinogenic amino acids, polyols, phytosterols, acylglycerols, mono- and oligosaccharides, glycosides, phenolic compounds (hydroquinone, kempferol), etc. This fact was consistent with the previously obtained data on the relationship between Fusarium resistance in oats (Avenasativa L.) and certain components of the metabolomic profile, such as acylglycerols, nonproteinogenic amino acids, galactinol, etc. Thus, our studies once again confirmed the possibility and effectiveness of the use of metabolomic analysis for screening the genetic diversity of accessions in the VIR collection, of Ae. tauschii in particular, in order to identify forms with a set of compounds in their metabolomic profile, which characterize them as resistant. Ae. tauschii accessions with a high content of pipecolic acids, acylglycerols, galactinol, stigmasterol, glycerol, azelaic and pyrogallic acids, campesterol, hydroquinone, etc., can be used for creating wheat and triticale cultivars with high resistance to fungal pathogens causing powdery mildew, brown rust, and yellow rust.